Analisis Pengaruh Variabel Moneter (Jumlah Uang Beredar, Nilai Tukar dan BI Rate) Dan Pengeluaran Pemerintah Terhadap Inflasi Di Indonesia - Silvester Adis Kristiawan (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to analyze at the effect of monetary policy is represented by the money supply, exchange rate and BI Rate and fiscal policy represented by government spending to inflation in Indonesia. The data used is inflation, money supply, exchange rates, interest rates and government spending. With this method of analysis Ordinary Least Square (OLS). Model studies have stated to have passed the test classic assumptions, with money supply variable research results and exchange rates had a significant negative influence on inflation in Indonesia, while the variable BI rate and government spending has a significant positive effect on inflation in Indonesia. The coefficient determination of 77.4%, meaning the ability of the independent variable in explaining its effect on the dependent variable amounted to 77.4%, while the remaining 22.6% is explained by other variables outside the model.Keywords: Money Supply, Exchange Rate, BI Rate, Government Spending